2021
DOI: 10.14444/8005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Protein Supplement on Paraspinal Muscles in Spine Fusion Surgery: A Randomized, Double-Blind, Placebo-Controlled Trial

Abstract: Background: Dysfunction and weakness due to atrophy of the paraspinal muscles is a major issue after posterior spinal fusion (PSF) surgery, resulting in pain and disability. Considering the role of protein in muscle regeneration, it seems that protein supplements after surgery may prevent muscle atrophy. To date, to our knowledge, no intervention study has investigated the effect of protein supplementation on the volume of paraspinal muscles, pain, or disability after PSF.Methods: In this randomized, double-bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 65 publications
4
14
0
Order By: Relevance
“…This study found that patients who had perioperative nutritional supplementation had increased cross-sectional areas of their paraspinal muscles, signifying less atrophy than the control group 26. This group later followed up these results by examining the effects of protein supplementation, as a part of an Enhanced Recovery After Surgery (ERAS) protocol 26. Patients who underwent posterior spinal fusion and provided with perioperative nutritional supplementation had higher rates of successful vertebral fusions 26.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…This study found that patients who had perioperative nutritional supplementation had increased cross-sectional areas of their paraspinal muscles, signifying less atrophy than the control group 26. This group later followed up these results by examining the effects of protein supplementation, as a part of an Enhanced Recovery After Surgery (ERAS) protocol 26. Patients who underwent posterior spinal fusion and provided with perioperative nutritional supplementation had higher rates of successful vertebral fusions 26.…”
Section: Discussionmentioning
confidence: 95%
“…Because of the hypermetabolic state, a patient is often in following lumbar spine surgery, protein supplementation may theoretically help maintain a proper balance and counteract the net loss due to increased energy utilization 26–28. Several studies have concluded that the protein intake required for recovery is not often met by the preoperative diet of a patient; thus patients may benefit from nutritional supplementation postoperatively 29–31.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations